The principle of virtual work and the third order wave on continua with second order constitutive equations - Beda, G. (Прикладная механика, 2010)
The generalized form of the principle of virtual work is obtained, when the virtual work is considered as a time integral of virtual power. The corresponding this form Euler – Lagrange equation includes the divergence of the Lie derivative of stress. So, the equation of motion on the stress rate field is one of the results of this paper. When bying studied the third order wave, a generalization of the acoustic tensor is obtained. The generalized acoustic tensor seems the most important result of these paper. This one can also be found by investigating the acceleration wave.